2011
DOI: 10.1021/jp202098k
|View full text |Cite
|
Sign up to set email alerts
|

Computational Study of the Deamination of 8-Oxoguanine

Abstract: Oxidation of guanine in DNA yields the nucleobase damage product 8-oxoguanine (8-oxoG), whose further oxidation gives other more stable products. In the present study, the mechanism for the deamination of 8-oxoG with H(2)O, 2H(2)O, H(2)O/OH(-), and 2H(2)O/OH(-) and for protonated 8-oxoG (8-oxoGH(+)) with H(2)O has been investigated using ab initio calculations. All structures were optimized at RHF/6-31G(d), MP2/6-31G(d), and B3LYP with the 6-31G(d), 6-31+G(d), 6-31G(d,p), 6-31+G(d,p), and 6-31++G(d.p) basis se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 46 publications
2
23
0
Order By: Relevance
“…Pathway F1 has the lowest overall activation energy of 201 kJ mol −1 compared to 232 kJ mol −1 for the pathway F2. The previous study of the deamination reaction of 8‐oxoguanine with 2H 2 O was found to be similar to this pathway where the overall activation energy is 220 kJ mol −1 at G3MP2 in the vacuum …”
Section: Resultsmentioning
confidence: 59%
See 3 more Smart Citations
“…Pathway F1 has the lowest overall activation energy of 201 kJ mol −1 compared to 232 kJ mol −1 for the pathway F2. The previous study of the deamination reaction of 8‐oxoguanine with 2H 2 O was found to be similar to this pathway where the overall activation energy is 220 kJ mol −1 at G3MP2 in the vacuum …”
Section: Resultsmentioning
confidence: 59%
“…Uddin et al found that the overall activation energy for the deamination of protonated guanine with H 2 O is 243 kJ mol −1 at G3MP2 . In another study, Uddin and Poirier found that the overall activation energy for deamination of protonated 8‐oxoguanine with H 2 O is 248 kJ mol −1 at G3MP2 which is in excellent agreement with energy barrier of protonated guanine . Yu et al studied the deamination reaction of protonated isoguanine with H 2 O, and they found that the overall activation energy is 217 kJ mol −1 at B3LYP/6‐311++G(d,p) .…”
Section: Resultsmentioning
confidence: 76%
See 2 more Smart Citations
“…[14] Besides experimental reports, computational studies have also been performed on the deamination reactions of amidine and nucleobases derivatives. [4,13,[27][28][29][30][31][32][33][34][35][36][37] Flinn and Poirier [4] carried out an extensive computational study on the catalytic deamination of formamidine with H 2 due to high activation energy barriers (> 210 kJ mol -1 at G2 theory) involved. For the deamination of formamidine with OH − , their results showed that deprotonation of formamidine by OH − , rather than deamination, is the most likely process.…”
Section: Introductionmentioning
confidence: 99%